Comparison of four commercial immunomagnetic separation kits for the detection of Cryptosporidium - Jeanne Claudeen Arona; Timothy J. Hall; Flyn Mckinnirey; Fei Deng (IWA Publishing, 2023)
Cryptosporidium spp. are protozoan parasites of significant health importance found in environmental waters globally. Four commercially available Cryptosporidium-specific immunomagnetic separation (IMS) kits used in various water sample matrices were analysed and compared. Beads were characterised by flow cytometry and tested for the recovery efficiencies for oocysts spiked into different matrices: river water sediment, clay sample, and filter backwash sample. Results showed that Dynabeads™ Cryptosporidium and Waterborne Crypto-Grab™ kits contained immunoglobulin IgM antibody-coated beads. In contrast, the BioPoint CryptoBead and the TCS Isolate kits contained immunoglobulin IgG antibody-coated beads. BioPoint CryptoBead was significantly coated with more antibodies and were able to capture oocysts more rapidly compared to the other beads. Recovery efficiencies of Dynabeads™, TCS Isolate® beads, and BioPoint CryptoBead ranged from 55 to 93% when tested against different sample matrices, with BioPoint CryptoBead resulting in the highest at 93% in reagent-grade water and Dynabeads™ at 55%, the lowest against clay samples. The Waterborne beads did not perform well on any samples, with recovery efficiencies ranging from 0 to 8%. Fluorescence microscopy analyses showed that both the IMS method and the sample matrix processed affect the quality of the membranes, with the cleanest samples for microscopy examination observed from BioPoint CryptoBead. HIGHLIGHTS Antibody types on magnetic beads and IMS methods differ across commercially available IMS kits.; IgG-coated BioPoint beads had 75-93% recovery efficiencies across the different sample matrices and gave the cleanest slides for microscopy.; IMS recovery efficiency is influenced by both the method used and the matrix analysed, with the purity of the slides affecting the results.;